2010
DOI: 10.1159/000318267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Polihexanide on Acute and Chronic Wounds for Antisepsis and Decontamination

Abstract: Polihexanide is an antimicrobial compound suitable for clinical use in critically colonized or infected acute and chronic wounds. Its beneficial characteristic is attributable particularly to its broad antimicrobial spectrum, good cell and tissue tolerability, ability to bind to the organic matrix, low risk of contact sensitization, and wound healing promoting effect. In addition, no development of microorganism resistance during polihexanide use has been detected to date, nor does this risk appear imminent. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 41 publications
0
47
0
3
Order By: Relevance
“…In contrast, a systematic review of the Cochrane Collaboration comparing silver-containing dressings against non-medicated dressings concluded that 'there is insufficient evidence to establish whether silver-containing dressings or topical agents promote wound healing or prevent wound infection' (Storm-Versloot et al, 2010). Polyurethane foam or biocellulose wound dressings containing 0.5 % PHMB were even more effective in reducing pain and bacterial burden in infected acute and chronic wounds compared with silver dressings (Eberlein & Assadian, 2010;Eberlein et al, 2012).…”
Section: Potential Use Of Cpc and Mstmentioning
confidence: 99%
“…In contrast, a systematic review of the Cochrane Collaboration comparing silver-containing dressings against non-medicated dressings concluded that 'there is insufficient evidence to establish whether silver-containing dressings or topical agents promote wound healing or prevent wound infection' (Storm-Versloot et al, 2010). Polyurethane foam or biocellulose wound dressings containing 0.5 % PHMB were even more effective in reducing pain and bacterial burden in infected acute and chronic wounds compared with silver dressings (Eberlein & Assadian, 2010;Eberlein et al, 2012).…”
Section: Potential Use Of Cpc and Mstmentioning
confidence: 99%
“…The same process was repeated using the lipophilic antiseptic PHMB, attached to the oil droplets of the same o/w emulsion. PHMB is a polymeric cationic antimicrobial agent and fast-acting broad-spectrum biocide against a wide range of both Gram-positive and Gram-negative bacteria [84,85,86,87]. PHMB was also shown to promote healing in acute and chronic wounds in combination with surgical debridement and clarification as well as with therapy of the underlying disease [85,86,88].…”
Section: Future Challenges To Improving Skin Antisepsismentioning
confidence: 99%
“…PHMB is a polymeric cationic antimicrobial agent and fast-acting broad-spectrum biocide against a wide range of both Gram-positive and Gram-negative bacteria [84,85,86,87]. PHMB was also shown to promote healing in acute and chronic wounds in combination with surgical debridement and clarification as well as with therapy of the underlying disease [85,86,88]. Roth et al [89] showed that PHMB has a dose-dependent positive effect on wound healing which is independent of its antiseptic properties [86,87,89,90].…”
Section: Future Challenges To Improving Skin Antisepsismentioning
confidence: 99%
“…Betaine has also been shown to effectively influence the communication within biofilm colonies (referred to as quorum sensing), by interfering with homoserine lactone manufacture. 18,19 Several studies have demonstrated Prontosan's (B. Braun) in vitro and in vivo wound healing and antiseptic efficacy; to date, resistance is not described, and it is distinguished from other antiseptics in having a very favorable biocompatibility index. It also has a low risk of contact sensitivity, and is sterile and odorless, and both the solution (for initial wound cleansing or as a soak) and gel (as a daily hydrogel dressing) are very versatile, easy to apply, and can be used with other dressing modalities.…”
Section: Prontosanmentioning
confidence: 99%
“…Of note, this agent has become the firstline instillation solution we use with NPWT. 18,19 Further experimental and clinical data are required to support the discontinuation of other antiseptics altogether, though. One concern with doing this is of course the theoretical development of resistance to an agent used exclusively.…”
Section: Prontosanmentioning
confidence: 99%